Neuromuscular adaptations to auto-regulated velocity-based versus fixed percentage-based squat training in sprinters - Guo, Hanzhao; Zhang, Lingfeng; Zheng, Zhanfei; Liu, Chang; Chen, Feng; Wu, Wenhai (Frontiers in Physiology, 2026)
PurposeTo compare auto-regulated velocity-based training (VBT) with traditional fixed percentage-based training (PBT) on neuromuscular performance in collegiate sprinters.MethodsTwenty resistance-trained males performed 6 weeks of back squat exercise 3 times per week. Both groups completed five sets of five repetitions with 3-min inter-set rest, matched for exercise selection and volume. The VBT group adjusted load based on real-time barbell velocity to maintain a target mean propulsive velocity of ∼0.54 m·s-1 (≈80% 1RM), whereas the PBT group trained with a fixed 80% of pre-intervention 1RM without further adjustment. Countermovement jump (CMJ), Standing long jump (SLJ), 20-m sprint times (T20-m), maximal strength (1RM back squat), and COD (T-test) were measured pre- and post-intervention.ResultsBoth groups significantly improved CMJ height (VBT: +7.8%, ES = 0.48; PBT: +6.7%, ES = 0.44), relative peak power output (VBT: +4.1%, ES = 0.85; PBT: +3.8%, ES = 0.35), SLJ performance (VBT: +1.0%, ES = 0.37; PBT: +1.8%, ES = 0.15), T20-m sprint times (VBT: −3.7%, ES = 1.30; PBT: −1.6%, ES = 0.51), maximal strength (VBT: +16.4%, ES = 1.57; PBT: +11.5%, ES = 0.94), and COD performance (VBT: −3.2%, ES = 0.54; PBT: −1.5%, ES = 0.39). VBT elicited significantly greater improvements than PBT in 1RM strength, T20-m, and COD performance (P < 0.05), whereas changes in CMJ and SLJ did not differ between groups (P > 0.05).ConclusionBoth training methods improved CMJ, SLJ, T20-m, 1RM back squat, and COD performance, but VBT may be slightly favorable for collegiate sprinters focusing on maximal strength, sprint performance, and COD compared to PBT.